Pathway of oxfendazole from the host into the worm: Trichuris suis in pigs. Issue 3 (December 2017) - Hansen, Tina V.A.; Williams, Andrew R.; Denwood, Matthew; Nejsum, Peter; Thamsborg, Stig M.; Friis, Christian
Abstract: It is well known that the efficacy of a single oral dose of benzimidazoles against Trichuris spp. infections in humans and animals is poor, but is currently still used in control programmes against human trichuriasis. However, the route of the benzimidazoles from the treated host to Trichuris remains unknown. As parts of adult Trichuris are situated intracellularly in the caecum, they might be exposed to anthelmintic drugs in the intestinal content as well as the mucosa. In this study, the pathway of oxfendazole and its metabolites was explored using a T. suis- pig infection model, by simultaneously measuring drug concentrations within the worms and the caecal mucosa, caecal tissue, caecal content and plasma of pigs over time after a single oral dose of 5 mg/kg oxfendazole. Additionally, for comparison to the in vivo study, drug uptake and metabolism of oxfendazole by T. suis was examined after in vitro incubation. Oxfendazole and metabolites were quantified by High Performance Liquid Chromatography. Multivariate linear regression analysis showed a strong and highly significant association between OFZ concentrations within T. suis and in plasma, along with a weaker association between OFZ concentrations in caecal tissue/mucosa and T. suis, suggesting that oxfendazole reaches T. suis after absorption from the gastrointestinal tract and enters the worms by the blood-enterocyte pathway. The fenbendazole sulfone level in T. suis was highly affected by the concentrations in plasma. In addition, correlations between drug concentrations in the host compartments, were generally highest for this metabolite. In comparison to oxfendazole, the correlation between plasma and content was particularly high for this metabolite, suggesting a high level of drug movement between these compartments and the possible involvement of the enterohepatic circulation. Graphical abstract: Image 1 Highlights: Trichuris suis accumulate OFZ, FBZSO2 and FBZ without significant metabolism in vitro . OFZ concentrations in plasma, tissue and mucosa are major determinants of OFZ levels in worms. FBZSO2 concentration in plasma is the main determinant of FBZSO2 levels in T. suis . The blood-enterocyte pathway is proposed as the major route for OFZ to reach T. suis .